Association between circHIPK3/miR-378a-3p/HDAC4 axis and osteoporotic fractures: A comprehensive investigation - Lei Wang; Zhen Sheng; Tao Yao (Journal of Orthopaedic Surgery, 2023)
Background Osteoporotic fractures (OFs) are a significant public health issue, which can lead to pain and impaired mobility. The underlying mechanisms of OFs remain unclear, but recent studies have suggested that the circRNA-miRNA-mRNA pathway may play a crucial role. Purpose This study aimed to investigate the potential involvement of the circHIPK3/miR-378a-3p/HDAC4 pathway in the pathogenesis of OFs. Methods We collected tissue and serum samples from 10 patients with OFs and 10 healthy controls. The expression levels of circHIPK3, miR-378a-3p, and HDAC4 were measured by qPCR and WB. Additionally, we quantified the serum levels of bone metabolism-related indicators (ALP, OC, TRAP, OCIF, ODF) using ELISA. Results Our results revealed significant upregulation of circHIPK3 and HDAC4 in both tissue and serum samples from OF patients compared with controls. Simultaneously, we detected a lower expression level of miR-378a-3p in OF tissues and serum than that in the control group. Furthermore, the serum levels of bone metabolism-related indicators ALP, TRAP, OCIF, and ODF were significantly higher in OF patients than in the control group. Interestingly, the serum level of OCIF was lower in OF patients than in the control group. Conclusion Our study provides important evidence for the involvement of the circHIPK3/miR-378a-3p/HDAC4 pathway in the pathogenesis of OFs. The upregulation of circHIPK3 and HDAC4 and downregulation of miR-378a-3p observed in OF patients suggests their potential regulatory effects on bone metabolism. Meanwhile, abnormal expression of serum bone metabolism-related indicators may contribute to the development of OFs by disrupting the balance of bone remodeling.